Integrating Service-Learning into the English as a Foreign Language Class - Mardijono, Josefa J. (Widya Mandala Surabaya Catholic University, 2016)
This paper is based on an explorative action research to find out how to integrate service-learning into the Written English IV class of the English Department and its possible impacts. It reveals the step by step procedure in implementing the service-learning, the activities carried out, and the challenges faced. The impacts viewed from the students’ sharing, the lecturer’s observation, and particularly the students’ written reflection, indicated that participating in the service-learning brought some positive impacts on the students. Service-learning is, thus, worth-considering in different contexts of EFL settings.